Nethouses protect cucumber plants from insect pests and increase yields in eastern Africa. Issue 5 (2nd September 2020) - Nordey, Thibault; Deletre, Emilie; Mlowe, Nickson; Martin, Thibaud
ABSTRACT: Vegetable cultivation in closed tunnels in the Tropics is impeded by high temperatures and poor pollination. This study compared the performance of cucurbits cultivated in open plots, in closed tunnels totally covered with small or large mesh nets (nethouse), and in open tunnels with a plastic film roof (rain shelter) in Tanzania over two seasons. Information was collected on climatic conditions, insect pest populations, vegetative development and yield. Temperatures were significantly higher under the tunnels than in the open plots during the day with few differences between the different tunnels. Insect pest populations were lower under nethouses than in open plots and under rain shelters, especially fruit flies. Higher marketable yields were obtained under nethouses with a small mesh (70.9 and 96.9 t.ha −1 ) and a large mesh (67.4 and 53.1 t.ha −1 ) than in open tunnels (12.9 and 9.1 t.ha −1 ) and in open plots (3.8 and 7.2 t.ha −1 ). Our results demonstrate that nets, especially with a small mesh size, provide versatile and efficient protection against major insect pests of cucumber, as well as a conducive environment for the development of the crop under local climatic conditions.